(untitled) - Hirotaro, Ota (Japan, 1972)
This book consists of the following many parts general survey history, characteristics, technical survey, of Japanese architecture; particular building types Shinto, Buddhist, house and castles architecture.
Keywords: Architecture,Gardens, Japanese,Gardens; Japan,Japan